Mekanisme Kerja Dry Needling pada Manajemen Nyeri - Henry Sugiharto (Fakultas Kedokteran Universitas Sriwijaya, 2019)
In the past 20 years, data in United States revealed that those who seek for acupuncture treatment has steadily increased to 12 million people (4% of population). Majority of those patients sought acupuncture for pain conditions (eg. musculoskeletal pain, headache and fibromyalgia) according to NHIS in 2007. Another interventional procedures using the similar filiform needles is dry needling. Dry needling itself has gained popularity in the last 10 years in United States. Acupuncture and dry needling has very little similarities but significantly different in its philosophy, theories and applications. Dry needling uses neurophysiological approach in its theory and neuromusculoskeletal assessments in its applications.